Aplicação das técnicas de gerenciamento da receita em serviços hoteleiros - Castro, Felipe de Vasconcelos (2010)
The service sector plays an increasingly important role for socio-economic development in many countries. The productive chain of tourism, with its various ramifications and great capacity for employment generation, is one of the members of this important sector. In this context, this study is dedicated to the Revenue Management application on enterprises of hotel services. This tool has the ability to contribute to development of this activity, wich is an highlight in the link of tourism. The basic concepts of RM has long guided trade relations and, more recently, associated with the democratization of information technology, began to be used consistently. Vast is the literature that portrays the results derived from the RM in service companies related to tourism, especially abroad. With the aim of understanding how this technology is used in Fortaleza, we selected three prominent hotels in the local market for the development of a multiple case study. Field research has evaluated the level of knowledge that companies hold on RM and the degree of implementation of the tool.